Hank The Cowdog: The Case of the Coyote Invasion - Book 56 - Erickson, John R. 1943-; Holmes, Gerald L. (New York : Viking, 2010)
When Loper puts him on Cheapo brand dog food and he gets in trouble for eating out of Sally May's birdfeeder, Hank the Cowdog hopes that he can get back in their good graces by thwarting the coyotes' plan to go after the chickens.
Keywords: Dogs -- Fiction; Ranch life -- Fiction -- Texas; Coyotes -- Fiction; Texas -- Fiction; Fiction